Desain Sistem Informasi Manajemen Perpustakaan (SIMPUSTAKA) Berbasis Lavarel Framework - Nabillah Syifauzzuhrah; Siti Zulaikha; Desi Rahmawati (Program Studi Manajemen Pendidikan, 2023)
The objective of this study is to develop a design for SimpusTaka as a website-based library using the Laravel Framework so that a conducive, systematic and computerized system can be created at the Ksatrya Lima Satu college foundation. SimPusTaka’s design was developed from the foundation's website, library guidebooks, and the existing studies. The primary emphasis of this research centers around the three phases of the Borg & Gall model’s development. The study began with data collection through interviews and literature reviews, followed by the planning and initial development stages of SimPusTaka. The findings suggest that the researchers utilized the Borg & Gall development stages to design SimPusTaka as a foundation for creating a system for managing library information that is based on the web using the Laravel framework. During the data collection phase, the researchers conducted a thorough literature review using previous studies, guidelines for library services, and the Ksatrya Lima Satu Higher Education Foundation website. Interviews were conducted with the YPKLS school librarian. At the SimPusTaka design stage, the researcher made a list of SimPusTaka features according to the suggestions given from the data collection stage, namely homepage features, search for books, about us, librarian, survey satisfaction, contact, registration form, login.